Post-capitalism(s). Signifier, meaning(s) and praxis - HIDALGO-CAPITÁN, Antonio; CUBILLO-GUEVARA, Ana (Utopía y Praxis Latinoamericana, 2023)
The aim of this paper is to give a meaning to the post-capitalism signifier. For this, we have carried out a conceptual analysis of the literature on the subject in the main languages during the last three decades from the "signifiers" approach. Subsequently, we have carried out a deconstruction of the meaning of capitalism signifier to construct a plural and coherent meaning of post-capitalism, with which to then turn to empirical reality in search of its praxis. From this we have concluded that post-capitalism is a set of forms of organization of socioeconomic systems that are subsequent and alternative to capitalism. These forms are characterized by the non-preeminence of the free market as a resource allocation mechanism, or by the non-preeminence of private property as an instrument for the accumulation of wealth, or by the non-preeminence of selfish rationality as a criterion for making economic decisions, or by a combination of these traits.